Integrating Linked Data into the Content Value Chain - Pellegrini, Tassilo (ACM, 2012)
Only a few media companies have so far (as of April 2012) publicly declared engagement in the area of Linked Data. Nevertheless among the chosen few are BBC Online, the New York Times, The Guardian and Reuters who utilize Linked Data to add significant value to the news production process. This paper discusses achievements and challenges in utilizing semantic metadata in the news production process. It illustrates how Linked Data can be integrated into the content value chain and provide added value to content-related workflows without necessarily disrupting them. This is insofar critical as publishing companies react very sensitively to radical changes in their working settings and are often very suspicious of technologically induced innovations. Given the fact that Linked Data is a highly technology driven phenomenon that incrementally incorporates the culture, speech and logic of the engineering discipline, it is necessary to translate the benefits of Linked Data into the thinking and understanding of the publishing sector by illustrating the intersections between the traditional editorial content value chain and Linked Data as a complementary resource to innovate existing products and services.
Keywords: Department Wirtschaft; Forschungsgruppe Media Business; Institut für Medienwirtschaft; Publikationstyp Schriftpublikation